Real-world evaluation of a novel technology for quantitative simultaneous antibody detection against multiple SARS-CoV-2 antigens in a cohort of patients presenting with COVID-19 syndrome. Issue 16 (8th July 2020) - Shaw, Andrew M.; Hyde, Christopher; Merrick, Blair; James-Pemberton, Philip; Squires, Bethany K.; Olkhov, Rouslan V.; Batra, Rahul; Patel, Amita; Bisnauthsing, Karen; Nebbia, Gaia; MacMahon, Eithne; Douthwaite, Sam; et al.
Abstract : An evaluation of a rapid portable gold-nanotechnology measuring SARS-CoV-2 IgM, IgA and IgG antibody response to spike 1 (S1), spike 2 (S) and nucleocapsid (N) antigens using serum from 74 RNA(+) patients and RNA(+) 47 control patients. Abstract : An evaluation of a rapid portable gold-nanotechnology measuring SARS-CoV-2 IgM, IgA and IgG antibody concentrations against spike 1 (S1), spike 2 (S) and nucleocapsid (N) was conducted using serum samples from 74 patients tested for SARS-CoV-2 RNA on admission to hospital, and 47 historical control patients from March 2019. 59 patients were RNA(+) and 15 were RNA(−). A serum (±) classification was derived for all three antigens and a quantitative serological profile was obtained. Serum(+) was identified in 30% (95% CI 11–48) of initially RNA(−) patients, in 36% (95% CI 17–54) of RNA(+) patients before 10 days, 77% (95% CI 67–87) between 10 and 20 days and 95% (95% CI 86–100) after 21 days. The patient-level diagnostic accuracy relative to RNA(±) after 10 days displayed 88% sensitivity (95% CI 75–95) and 75% specificity (95% CI 22–99), although specificity compared with historical controls was 100% (95%CI 91–100). This study provides robust support for further evaluation and validation of this novel technology in a clinical setting and highlights challenges inherent in assessment of serological tests for an emerging disease such as COVID-19.